1997
DOI: 10.1002/(sici)1098-1004(1997)9:4<332::aid-humu5>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a splice site mutation (2789+5 G>A) associated with small amounts of normal CFTRmRNA and mild cystic fibrosis

Abstract: A splicing mutation was identified at the +5 position of the splice donor site of exon 14b of CFTR in CF patients in a consanguineous family that is remarkable for unusually mild disease. Quantitative studies of nasal epithelial mRNA revealed that homozygotes for the spice site mutation produced approximately 4% of the normal amount of normally-spliced CFTR. We propose that this small amount of normally spliced mRNA is associated with synthesis of some normal CFTR protein, and accounts for the mild phenotype. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…First, concerning the genotype-phenotype relationship, different clinical features in class V patients (age at diagnosis, current age, etc.) indicated a milder phenotype compared with CF-F508del patients in agreement with previous reports 25,26 and also with c.580-1G4T patients, although in this case statistical analysis was unavailable. Nevertheless, we have also observed some severe clinical complications in class V patients probably attributable to the aging process; we should keep in mind that the c.2657 þ 5G4A CF patients analyzed in this study are in the upper range of the life expectancy among CF patients.…”
Section: Discussionsupporting
confidence: 91%
“…First, concerning the genotype-phenotype relationship, different clinical features in class V patients (age at diagnosis, current age, etc.) indicated a milder phenotype compared with CF-F508del patients in agreement with previous reports 25,26 and also with c.580-1G4T patients, although in this case statistical analysis was unavailable. Nevertheless, we have also observed some severe clinical complications in class V patients probably attributable to the aging process; we should keep in mind that the c.2657 þ 5G4A CF patients analyzed in this study are in the upper range of the life expectancy among CF patients.…”
Section: Discussionsupporting
confidence: 91%
“…An example is the relatively common SGLT2 IVS7 ϩ5 gϾa mutation, a donor splice site mutation that was found to be associated with some residual glucose reabsorption and comparably low glucose excretion. It is well known that this type of mutation results in both abnormally and normally spliced mRNA with the effect of a decreased amount of the gene product with normal kinetic properties (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of the CFTR gene that causes CF, over 1,000 mutations have been identified (34), yet only a small number of CFTR genotypes are associated with a milder clinical phenotype (3,5,(21)(22)(23)(24)(25). The effect of CFTR genotype on phenotype seems to relate to the functional effects of CFTR genotypes on CFTR production with very low levels of CFTR associated with a severe phenotype and intermediate levels of CFTR associated with milder CF (25,35,36). Despite this, there is evidence that the clinical course in patients with the same CFTR genotype is highly variable, and family-based studies have suggested that genetic factors that code outside of CFTR may modify the CF phenotype (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a severe CFTR genotype have very low levels (Ͻ 3%) of functioning CFTR protein, which leads to a more severe CF phenotype. Patients with a mild CFTR genotype have a milder clinical phenotype that is most likely due to the expression of increased amounts (5-13%) of functioning CFTR protein (25,35,36). Because CFTR influences the transport of GSH into the ELF, patients with CF with GCLC variants associated with greater GSH production, in the setting of more functioning CFTR, should have higher levels of GSH in the ELF and enhanced protection against oxidant-induced lung injury.…”
Section: Discussionmentioning
confidence: 99%